Covid-19 : uma avaliação no risco de transmissão nos serviços de alimentação e nutrição na Região Metropolitana de Cuiabá-MT - Silva, Priscilla Aparecida Alves da (2023)
The world is facing the COVID-19 pandemic, caused by SARSCoV-2 (new coronavirus) and to prevent the transmission of this virus, it was necessary to adopt isolation and social distancing measures. However, workers in the food production chain are considered essential and therefore could not leave their workplaces. In this context, the present study aims to review the topic addressed, as well as to assess the risk of transmission of COVID-19 in food services in the metropolitan region of Cuiabá-MT. For data collection, points such as: physical structure of the establishment, personal hygiene of the handler, general worker protection measures, use of Personal Protective Equipment, food storage and management/administrative area in supermarkets, butchers and bakeries, bars and restaurants, with three units of each type of establishment. The results obtained were analyzed using Excel and PowerBi (Microsoft®) tools, obtaining graphs with percentages. In a general assessment, it was observed that the establishments were equal in terms of non-compliance, a fact corroborated by the Analysis of Variance, which provided a value of p=0.479 for the questions and p=0.635 for the establishments, concluding that there is no difference statistically significant between the groups or conditions evaluated. However, despite a statistically insignificant difference, the butchery group was the one that presented the highest percentage of non-compliance (44.22%, in general) and within the points analyzed, hand washing conditions was the highest Critical Control Point ( 60.56% was the average of nonconformities of all evaluated establishments). It was concluded that although health authorities and companies implement measures to prevent the spread of SARS-COV2 (distancing of at least 1.5m, guidance on proper hand washing, use of alcohol gel and training on Good Practices of Manufacturing and preventive measures for COVID-19), which are often not followed by employees, thus increasing the risk of transmission of COVID-19 among them. In addition, there was a need for local inspection to be more active, in a preventive and repressive way.